Internet connectivity disruption in Benin (Benin) - Voidly (2026)
CRITICAL severity disruption detected in Benin. Confidence: 65%. Data sourced from IODA.
Network Disruption Incident ID: BJ-2026-0017
Keywords: internet disruption; BJ; disruption; critical